Decentralized Control of a Group of Homogeneous Vehicles in Obstructed Environment - Vyacheslav Pshikhopov; Mikhail Medvedev; Alexander Kolesnikov; Roman Fedorenko; Boris Gurenko (Journal of Control Science and Engineering)
The presented solution is a decentralized control system with a minimal informational interaction between the objects in the group. During control and path planning the obstacles are transformed into repellers by the synthesized controls. The main feature distinguishing the developed approach from the potential fields method is that the vehicle moves in the fields of forces depending not only on the mutual positions of a robot and an obstacle but also on the additional variables allowing solving the problem of robot’s path planning using a distributed control system (Pshikhopov and Ali, 2011). Unlike the work by Pshikhopov and Ali, 2011, here an additional dynamic variable is used to introduce stable and unstable states depending on the state variables of the robot and the neighboring objects. The local control system of each vehicle uses only the values of its own speeds and coordinates and those of the neighboring objects. There is no centralized control algorithm. In the local control algorithms the obstacles are represented as vehicles being a part of the group which allows us to unify the control systems for heterogeneous groups. An analysis was performed that proves existence and asymptotic stability of the steady state motion modes. The preformed simulation confirms the synthesis and analysis results.